STUDY OF THE COMPETITIVENESS AND SUSTAINABILITY OF THE MSME CLUSTER IN THE CITY OF SEMARANG - Ade Nantera; Tri Widayati (Universitas 17 Agustus 1945 Semarang, 2023)
Development of MSME Clusters in Semarang City is carried out to support the activities of MSME actors who are grouped into various types. This research was conducted by taking a sample of 70 MSME actors in various clusters. The competitiveness and sustainability of the clusters are determined using the AHP (Analytic Hierarchy Process) Method. From the results of the analysis it was found that Clusters in Semarang City, it can be seen that based on the HR variable, all clusters in Semarang City fall into the criteria/category of Sustainable Clusters. However, when viewed from the competitiveness variable, there are 3 (three) clusters that fall into the less sustainable category, namely Metals, Tourism, and Furniture. So, in general, the results of the cluster categories in the city of Semarang show that the problems facing cluster sustainability are more like an inability to compete